Lactobacilli as additional cultures in cheese making - N. P. Sorokina; I. V. Kucherenko; A. L. Bruckaya (Пищевые системы, 2024)
Production of cheeses from thermally processed milk at an industrial scale is impossible without using commercial bacterial starter cultures that include a limited number of species and strains of microorganisms. This leads to the fact that sensory indicators of mass-produced cheeses practically do not differ. Traditional cheeses from unpasteurized milk are distinguished by more pronounced and diverse tastes. Scientific literature describes the significant taxonomic variety of microbiota of traditional cheeses, including non-starter lactobacilli. Sensory indicators and safety of cheeses directly depend on the composition of this microbiota. This study examines the main moments of the taxonomic reform of lactobacilli, which resulted in union of two families Lactobacillaceae and Leuconostocaceae, and division of the genus Lactobacillus into 25 genera. New description of the family and several species of lactobacilli used in starter cultures is given. The authors demonstrate the complex autochthonous microbiota of cheeses and a possibility of stabilization of fermentation upon cheese making from raw milk and improvement of their quality without losing individuality due to the introduction of selected autochthonous additional cultures. When cheeses are made from pasteurized milk, these cultures improve sensory characteristics of a product and impart the original flavor to them. Several studies show that probiotic bacteria intensively develop and maintain viability for a long time even in long-ripened cheeses. Such cheeses can be carriers of live probiotics and their metabolites that are beneficial for the consumer health. This review summarizes information about promising directions of extension of the species spectrum of additional cultures for creation of domestic starter cultures for cheese making. Taking into consideration that microbiology of cheese making is quite a wide field that is not fully studied, the review does not claim to be the comprehensive analysis of all existing approaches.